TEACHER MOTIVATION IN TEACHING AT RURAL AREA - Rigel Sampelolo; Deny Dominikus (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The objective of the study was to find out the teacher motivations in teaching at rural area. The participants of the research will be four non-permanent teachers that have been teaching in rural area. Meanwhile, this study is a qualitative method which is to find out what are the teacher motivations in teaching at rural area. Those teachers will be determined by using purposive technique sampling. The researcher uses interviews to find out the results of the research. The analyzed result of the data showed, if the researcher found there are three motivations that can motivated the teacher in teaching at rural area. Meanwhile they are consisting of; the natives, self-desire, and the last one which is, life condition and the environment. Based on the result above, there are three factors that can motivate the non- permanent teachers. The first one which is categorized as the intrinsic motivation consists of self-desire. Meanwhile, the second is categorized as the extrinsic motivations which are the natives, and, the life condition and the environment. From two kind of the motivations mentioned above, it is clear if the intrinsic and extrinsic motivation factor can motivate the non-permanent teachers when performing their duty in rural area.